SISTEM PAKAR UNTUK DIAGNOSA PENYAKIT KEJIWAAN DENGAN MENGGUNAKAN METODE TEOREMA BAYES - Yul Hendra; Anju Parapat; Dedi Juniansha (Jurnal Sistem Informasi dan Informatika (Simika), 2020)
One way to detect psychiatric illnesses is to utilize advanced and modern technology, namely the field of study of Artificial Intelligence (AI) that is able to mimic human intelligence. One part of artificial intelligence is an expert system (expert system). In general the expert system (expert system) is one of the fields of computer science that utilizes computers so that they can behave intelligently like humans. This system seeks to adopt human knowledge into computers, so that computers can solve problems as is usually done by experts. The expert system will provide a list of symptoms until they can identify the object based on the answers received. This system is intended for early diagnosis of 4 types of mental illness, namely: Schizophrenia, Psychopaths, Obsessive and Depression. The processed data is obtained from psychiatrists. and the expected outcome of this system is to be able to detect psychiatric diseases early with the help of a system in which knowledge is taken from the knowledge of a psychiatrist.